Passagerarbehov i självkörande bilar: Ett arbete inom produktutveckling på Volvo Personvagnar AB - Blom, Philip (My University, 2019)
Abstract The aim of this study is to obtain insight as to how the development of a foldable table in autonomous cars can be designed and constructed. Moreover, it includes the aspects of product development based on the underlying flaws of existing product or change in customer needs. In order to collect suggestions a customer survey was sent out to over hundred of product developers and the data was collected and put together accordingly in a matrix. Based on the customer survey a requirement specification was made. A representation of the product divided in functions was concluded in a function tree. With the use of an analysis of the current competitors and their similar products in the area together with brainstorming, all the solutions to the functions was collected in a morphological matrix. The morphological matrix was used to create twelve different, mostly innovative concepts. The concepts was made with various suggestions as to where they could be attached in the cars interior. An evaluation matrix was constructed based on aspects such as stability, flexibility, simplicity to use amongst others. All the twelve concepts were given a final score in which the most fitting concepts was picked out in discussion together with the company. A design of the part that would attach to the table in order to obtain desired requirements and needs was made. It has not yet been decided exactly how the interior in the future of autonomous car should look. Therefore it was concluded that since the difference in total points of most of the concepts were just by a few points, that different concepts could be chosen depending on the aim of the development in the future and also in which part i the interior the aim is to put the table. Also, the concepts could with easily be used in regular cars if the safety regulations would allow it.
Keywords: Produktion; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Production; Sustainable Development; Innovation & Entrepreneurship; Mechanical Engineering